Hold Your Horses: Temporal Multiplexity and Conflict Moderation in the Palio di Siena (1743–2010) - Operti, Elisa; Y. Lampronti, Shemuel; Sgourev, Stoyan V. (Organization Science, 2020)
The paper elaborates the concept of temporal multiplexity, defined as the overlaying of ties of different duration, such as transient employment and enduring organizational ties. This concept is instrumental in resolving long-standing challenges in network research, such as capturing the interplay between different levels of analysis or time horizons. This is made possible by longitudinal network and mobility data (1743–2010) from the Palio di Siena—the famous horse race in Siena, Italy. The outcome of interest is Palio-related collective violence. The analysis shows that relationally loaded organizational ties of rivalry or friendship increase the likelihood of incidents, whereas mobility along the same lines reduces it. The results support sociological arguments that symmetrical social space of friendship or rivalry is conducive to conflict. Mobility is a factor of moderation—by connecting employers within the actor and transferring relational content between them, it creates misalignment between the assumption of a role and fulfillment of its expectations. Mobility relaxes the relational constraints of jockeys, reducing their compliance with bellicose demands. The uncertainty resulting from mobility may have a collective benefit that is ignored by employers: the moderation of conflict.